2022
DOI: 10.3390/nano12203670
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Dental Applications of Titania Nanoparticles: An Overview

Abstract: Currently, titanium oxide (TiO2) nanoparticles are successfully employed in human food, drugs, cosmetics, advanced medicine, and dentistry because of their non-cytotoxic, non-allergic, and bio-compatible nature when used in direct close contact with the human body. These NPs are the most versatile oxides as a result of their acceptable chemical stability, lower cost, strong oxidation properties, high refractive index, and enhanced aesthetics. These NPs are fabricated by conventional (physical and chemical) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 343 publications
0
20
0
Order By: Relevance
“…Recently, the modified TiO 2 NPs have been used for the delivery of various anticancer drugs, such as temozolomide, cisplatin, doxorubicin, and daunorubicin. 8,182 For instance, Han et al reported the synthesis of poly(acrylic acid)-calcium phosphate modified TiO 2 NPs (TiO 2 NPs@PAA-CaP) for the efficient drug delivery of doxorubicin (DOX). 183 This surface modification of TiO 2 NPs resulted in a significant enhancement of DOX loading and encapsulation up to eight times, compared to that of unmodified TiO 2 NPs.…”
Section: Biological Applications Of Modified Tio2npsmentioning
confidence: 99%
“…Recently, the modified TiO 2 NPs have been used for the delivery of various anticancer drugs, such as temozolomide, cisplatin, doxorubicin, and daunorubicin. 8,182 For instance, Han et al reported the synthesis of poly(acrylic acid)-calcium phosphate modified TiO 2 NPs (TiO 2 NPs@PAA-CaP) for the efficient drug delivery of doxorubicin (DOX). 183 This surface modification of TiO 2 NPs resulted in a significant enhancement of DOX loading and encapsulation up to eight times, compared to that of unmodified TiO 2 NPs.…”
Section: Biological Applications Of Modified Tio2npsmentioning
confidence: 99%
“…Various types of nanomaterials have been found to imitate host tissue properties in studies, albeit there is no knowledge of such features among dentistry groups. [ 21 24 ] As a result, the current analysis center on the possessions of various metal- and polymer-based nanomaterials[ 22 ] utilized in dental adhesives and restoratives, acrylic resins, period ontology, tissue engineering, endodontic, and implant dentistry. [ 25 26 ]…”
Section: R Esultsmentioning
confidence: 99%
“…Currently, a large number of technological processes use nano-sized materials of the titanium dioxide (ТіО 2 ) amphoteric compound. In recent years, the world market of this material is estimated at approximately ten million tons per year, of which a large sector is occupied by the food, medical and pharmaceutical industries (Irshad et al, 2021;Mansoor et al, 2022). Thus, ТіО 2 is widely used in food coloring, cosmetic and hygiene products, nanomedical reagents, and pharmaceutical products (titanium dioxide food additive is marked with E171 code).…”
Section: Introductionmentioning
confidence: 99%